PENGARUH BIOINSEKTISIDA EKSTRAK KULIT JERUK NIPIS TERHADAP KEMATIAN HAMA ULAT GRAYAK DAN BIOMASSA TANAMAN SAWI HIJAU - Khairun Nisa Rizkha Febriani; Diah Karunia Binawati (FMIPA : Universitas PGRI Adi Buana, 2016)
This study on the effect of bioinsektisida lime peel to the death of pests armyworm (Spodoptera litura) and biomass plants green cabbage which aims to determine the effect of the death of armyworm (Spodoptera litura) and biomass plants green cabbage, in addition to providing information to farmers to take advantage of natural ingredients, namely lime peel. Lime peel contains limonene that can be used as a biopesticide. Limonene is a poison that spreads to the nervous tissue, which causes paralysis (paralysis) and will eventually die. This study is based on a completely randomized design (CRD), which consists of 4 treatments 6 replications with 192 samples armyworms and 24 of mustard. Methods of data analysis in this research is test Annova and continued to LSD. This study was made with a concentration of 0%, 3%, 6% and 9%. Lemon peel extract obtained by maceration for 3 days using 96% alcohol. The treatment of lime peel extract by spraying 1ml / 100ml. Results showed no effect of lime peel extract biopesticide against armyworm pest mortality, at a concentration of 9% showed a significant number of deaths. While on green cabbage plant biomass was no effect of lime peel extract so it did not proceed to LSD. Keywords : bioinsectisida, orange peel Lime, Death armyworm , Biomass Plants Green Cabbage